CONCEPTE MANAGERIALE ÎN ACTIVITATEA TELEVIZIUNII PUBLICE - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2009)
The Authors make an attempt to link general principles of the management to the objectives of the public TV and radio institution. The basic functions of management–planning, organizing, administering, controlling and evaluating are implemented to the daily practices of the public TV. The standard organizational chart of TV and radio institutions in Europe is also presented. The other managerial concepts are analyzed, such as the strategy of TV and Radio, organizational culture, stimulation and especially motivation of the employees, being exposed the main requirements to this important aspect – motivation of the personnel.